Associations among dietary supplement use, dietary intake, and chronic health conditions of older adults - Weeden, Allisha Marie (Kansas State University, 2008)
The frequency of dietary supplement use has increased in recent years, especially among older adults. National studies estimated 60-65% of older adults were using at least one dietary supplement, typically a multi-vitamin, multi-mineral (MVMM) supplement. Dietary supplement use has been reported to improve the micronutrient intakes of older adults. The current research study focused on the use of dietary supplements, dietary intakes, and impact of vitamin/mineral (VM) supplements on the nutrient intakes of older Kansans. Volunteer subjects, 60+ years of age, were recruited from 35 senior centers across Kansas. Subjects completed a questionnaire asking for demographic information, current health status, and dietary supplement use. Dietary supplement use was verified for 319 subjects. Two subsequent 24-hour diet recalls were completed by 312 subjects. The sample population was primarily white, non-Hispanic females. Nearly 86% of participants used at least one dietary supplement; most commonly MVMM, calcium, vitamin D, and fish oil. Dietary intake analyses compared intakes of dietary supplement (DS) users to non-dietary supplement (NDS) users. DS subjects consumed significantly higher dietary intakes of carbohydrate, fiber, vitamin A, and zinc than NDS subjects. The NDS group consumed undesirably higher intakes of total fat, saturated fat, and sodium. These results support previous findings that DS users consume healthier diets. The impact of VM supplement use on micronutrient intake compared only the intakes of subjects using VM supplements (n=263) to the Dietary Reference Intakes (DRI). Subjects were most likely to have inadequate dietary intakes of vitamin D, calcium, vitamin E, and magnesium. All micronutrient intakes were improved with the inclusion of VM supplements; most improved were vitamin E, folic acid, vitamin D, vitamin B6, and calcium. Despite supplementation, nearly half of subjects still exhibited low intakes of vitamin D, calcium, and magnesium. Supplementation did not consistently exceed the Tolerable Upper Limit established by the DRIs for most nutrients. In conclusion, dietary supplement use was very common in the sample population, DS subjects had generally healthier diets, and VM supplement use improved micronutrient intake without contributing to concern for toxicity.
Keywords: Nutrition; Dietary supplements; Elderly; Vitamins and minerals; Kansas; Dietary intake; Health Sciences, Nutrition (0570)